DIRIJYORNING KASBIY XUSUSIYATLARI - Tnibayev, P.K. (SCIENCE and SOCIETY, 2023)
Comparing a bandleader with a performer, an orchestral team is like his musical instrument. The ability to manage this collective, to concentrate each performer on the way to one goal, to skillfully perform a work and attract the attention of listeners, requires painstaking work from the bandleader. However, to go through this process, the bandleader will need several functions. This article will provide information about what the pedagogical characteristics of the bandleader are and what can be achieved with the help of them.
Keywords: conductor; teacher; orchestra; leadership; skills; orchestra team